Dramaturgi Di Balik Kehidupan Akun Alter Twitter Dramaturgy Behind Twitter Alter Accounts - Kirana, Nevi Dwi; Pribadi, Farid (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This article discusses the practice of Dramaturgy theory carried by the owners of alter Twitter accounts. In the modern era, communication technology is not only used to facilitate human work. Communication technology is also used to make it easier for humans to interact with each other. That practice of social interaction does not only occur in the real world but also in the virtual world. Many dramaturgical theory practices appear in cyberspace, one example is alter accounts on Twitter. This research uses descriptive qualitative method. The researcher creates a description based on the facts, characteristics, and relationships between the phenomena. The data collection method used is observation and interview. This study indicates that the two sources have something in common, that is, to make their alter accounts on Twitter a place to show a side of themselves that they cannot show in the real world. On the front stage, they build a self-image by posting sensual photos and videos in revealing clothes accompanied by supporting captions. However, on the back stage, these two sources show the opposite side, by dressing neatly, covering their genitals, acting politely and also having good manners.